2011
DOI: 10.1111/j.1365-2125.2011.04038.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of two formulations of omeprazole administered through a gastrostomy tube in patients with severe neurodevelopmental problems

Abstract: AIMS Omeprazole is often administered through a gastrostomy tube as either (i) a Multiple Unit Pellet System (MUPS (R)) tablet disintegrated in water (MUPS (R) formulation), or (ii) a suspension in 8.4% sodium bicarbonate (suspension formulation). This bioavailability study evaluates this practice in tube-fed patients with severe neurodevelopmental problems. METHODS Nonblinded, two-phase cross-over trial. RESULTS In seven of 10 patients, bioavailability was higher for the suspension formulation than for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…This is in agreement with reported delays in in vivo drug absorption from enteric coated PPI products. Boussery et al showed that the time to reach maximum plasma drug concentration (tmax) was 0.57 ± 0.16 and 2.36 ± 1.74 hours for immediate release omeprazole suspensions and enteric coated omeprazole MUPS tablets respectively in patients with severe neurodevelopmental problems (K. Boussery et al, 2011). In addition, the MUPS tablets showed high inter-individual variation in reaching tmax (ranging from 1 to 6 hours).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with reported delays in in vivo drug absorption from enteric coated PPI products. Boussery et al showed that the time to reach maximum plasma drug concentration (tmax) was 0.57 ± 0.16 and 2.36 ± 1.74 hours for immediate release omeprazole suspensions and enteric coated omeprazole MUPS tablets respectively in patients with severe neurodevelopmental problems (K. Boussery et al, 2011). In addition, the MUPS tablets showed high inter-individual variation in reaching tmax (ranging from 1 to 6 hours).…”
Section: Discussionmentioning
confidence: 99%
“…Iwasaki et al, 2004) and the in vitro t80 values are 0.8-1.0 and 1.5-1.6 hours in pH 6.8 phosphate buffer and mHanks buffer respectively. The reported in vivo tmax values for omeprazole products range from 1.9 to 4.0 hours (K. Boussery et al, 2011;S. Karim et al, 2014;Z.…”
Section: Discussionmentioning
confidence: 99%
“…This variability might be due to genetic polymorphism of the cytochrome P450 (CYP) isoform CYP2C19. [17][18][19][20] Additionally, demographic data of subjects; age, weight, height and concomitant medication could add to the high inter-individual variability.…”
Section: Discussionmentioning
confidence: 99%
“…This tablet formulation is a Multiple Unit Pellets System (MUPS ® ) containing enteric-coated pellets that protect the acid-labile omeprazole against protonation in the stomach [ 31 ]. Boussery et al [ 32 ] showed that a suspension formulation of omeprazole (extemporaneous formulation) seemed to be more favourable with regard to plasma concentration-time profiles compared to the MUPS ® formulation. This highlights the complexity of ensuring the efficacy of proton pump inhibitors when being manipulated.…”
Section: Discussionmentioning
confidence: 99%